Building and Development of Business Entries Owned by the Village in Sumedang District West Java Province - B., Asri; Syafri, Wirman; Pitono, Andi; Achmad, Mansyur (International Journal of Science and Society, 2024)
Village-Owned Enterprises (BUMDes) are established as a manifestation of the government's commitment to fostering self-reliance and bolstering the local economy. However, it is evident that not all BUMDes have effectively initiated and executed commercial endeavors, thus failing to yield desired economic outcomes. This underscores suboptimal implementation of coaching and development initiatives. This research uses a qualitative method with a case study approach. For this reason, the research location was determined in Sumedang Regency with a case sample of 4 (four) BUMDes in different sub-districts which represent BUMDes qualifications, namely pioneer, beginner, developing and advanced. Data was collected through interview techniques, observation and documentation and then analyzed qualitatively. The formulation of BUMDes development and development strategies is carried out through SWOT analysis. The research findings indicate that the reasons for the inactivity and lack of development among many BUMDes in Sumedang Regency include: (1) low human resource capacity; (2) weak legal aspects; (3) insufficient institutional relationships; (4) the formation of BUMDes often driven by formalistic reasons; and (5) limited marketing networks. Effective strategies for BUMDes development should encompass: (1) human development through enhancing human resource capacities; (2) enterprise development through promoting village potential, facilitating cooperation and partnerships, strengthening marketing networks via digital marketing; (3) environmental development through mapping natural resource-based village enterprises; and (4) institutional development through optimizing the implementation of regulations concerning villages and BUMDes, collaboration in nurturing and developing BUMDes, facilitating BUMDes legality, reinforcing village consultations, and strengthening institutional relationships of BUMDes.